Mendicant Brethren and Master Builders: The Building’s History of the Mendicant Orders in Medieval Denmark - Larsen, Morten (Collegium Medievale, 2019)
This article looks into the building’s history of the mendicant friaries of medieval Denmark with the aim of investigating distinct phases of development or decline. It is the article’s suggestion that the overall characterization of the building’s history can be divided into three main periods distinguished by the level of building intensity. The reasons behind the fluctuating tendencies are discussed, and despite the primary causes should be viewed in an overall religious, economical, and political perspective, the importance of contextually significant factors within each convent are emphasized.